ANALISIS EKONOMI RANCANGAN PLTS UNTUK KAWASAN WARISAN BUDAYA DUNIA JATILUWIH - Sinaga, P. M.; Ariastina, W. G.; Sukerayasa, I W.; Giriantari, I. A. D.; Setiawan, I N.; Satya Kumara, I N. (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUM, 2023)
Bali is a province in Indonesia that is progressive in utilizing renewable energy, by making a policy to create Bali Clean Energy, which aims to develop renewable energy including solar energy. Even though several Solar Power Plant developments have been carried out in Bali, it still needs to be accelerated in its application to achieve the set targets. In this study, the Jatiluwih Heritage Area was chosen as the location for designing a Rooftop solar power plant. Jatiluwih is a Village that became a World Cultural Heritage designated by UNESCO in 2012. The methods used in this research are interviews, literature studies, and scientific studies based on related journals. This study uses two scenarios, namely the load usage scenario and the roof area scenario. There are 45 buildings that have tourism activities in the Jatiluwih DTW area, with a daily electricity requirement of 225.37 kWh/day. Based on the criteria for installing a Rooftop Solar Power Plant, there were five buildings that met the criteria, namely Dukuh Batur Villa, Teras Subak Homestay, Warung Dhea, Iga Lawar Restaurant, and Bhuana Agung Restaurant. Based on the investment feasibility study using the Net Present Value, Profitability Index, and Payback Period methods, it shows that the investment in designing a Rooftop Solar Power Plant with a scenario based on load requirements has 2 feasible buildings, namely the Iga Lawar Restaurant and Bhuana Agung Restaurant, and based on the roof area scenario it shows the design investment Solar Power Plant Jatiluwih World Cultural Heritage Area is not feasible to implement.